Tingkatkan Fokus dengan Latihan Buttoning Skills pada Anak Mild Intellectual Disability - Nadira Khairunnisa; Nurul Hartini (Universitas Negeri Surabaya, 2022)
Children with intellectual disabilities have deficits in generalmental abilities due to insignificant cognitive development.The deficits result in weak attention functions that difficultymaintaining focus and are easily distracted. Therefore, theyfailed to meet standards in responsibility including daily lifeaspects. Implementing behavior modification enhancesmastery of daily life skills and also training focuses in orderthat children become more independent. This study aims toexamine whether buttoning skills practice could increasefocus on intellectual disability children. The experimentalapproach was carried out with a single case AB withbackward chaining technique assisted by prompting andgiving positive reinforcement. The participant was a 9-yearold girl with the initials ZR who was diagnosed with mildintellectual disability. Assessment based on accomplishmentfollowing the stages systematically. The results show there isan improvement trend in mastering buttoning skills. This isdue to appropriate positive reinforcement being selected thatmotivated participants to focus on completing tasks.Repetition makes participants become more acclimated towear button-up clothes. This skill practice could be an optionto encourage focus on intellectual disability children. Anak dengan intellectual disability mengalami defisit intelektual sebab perkembangan kognisi yang tidak optimal. Kondisi ini menyebabkan lemahnya fungsi atensi yang merupakan faktor signifikan dari perkembangan kognitif. Akibatnya anak mengalami hambatan pada kemampuan dalam keterampilan adaptif, sosial serta konseptual. Akan tetapi anak mild intellectual disability masih dapat dibina walau perlu pendampingan. Mereka dapat diajarkan keterampilan sehari-hari untuk meningkatkan kemandirian. Keterampilan harian self-help dressing menjadi salah satu kebutuhan, termasuk berlatih memasang-melepas kancing (buttoning skills). Buttoning skills membutuhkan tahapan yang tersistematis sehingga membantu anak berkonsentrasi. Penelitian ini adalah single case AB design pada anak mild intellectual disability berusia 9 tahun. Intervensi yang digunakan adalah backward chaining dibantu teknik prompting dan pemberian positive reinforcement. Hasil buttoning skills dengan intervensi yang ditetapkan mendapatkan gambaran adanya peningkatan keterampilan serta membangun fokus dan dorongan pada anak.